Evaluation of gastroprotective activity and acute toxicity of Solidago chilensis Meyen (Asteraceae) - Bucciarelli, Alejandro (2010)
Context: Solidago chilensis Meyen (Asteraceae) is widely used in South America in traditional medicine as an anti-inflammatory and diuretic, and to treat gastrointestinal disorders. However, no scientific evidence exists in literature to corroborate the therapeutic use of the plant. Despite its traditional uses, no reports are available on the safety of this utilization or on the relationship between the pharmacological activities and its phytochemical compounds. Objective: This study investigates for the first time the acute toxicity and the gastroprotective effect of the aqueous extract from inflorescences of S. chilensis. Materials and methods: The gastroprotective activity was evaluated in mice subjected to ethanol-induced gastric ulcer model at 125, 250, 400, 800, 1200, and 2000mg/kg doses. Acute toxicity study was performed at one dose of 2000mg/kg. At the end of the exposure behavioral and functional parameters and motor activity were assessed in all animals. Results: Results demonstrated that the extract exhibited a significant antiulcer activity when given at 125-2000mg/kg (P<0.05), but did not show acute toxicity in mice treated with 2000mg/kg p.o. Discussion and conclusion: This study demonstrated that the oral administration of S. chilensis aqueous extract prevents the formation of gastric lesions caused by an aggressive factor as ethanol but does not produce toxicity by acute exposure in mice. These promising results support a better pharmacological study of S. chilensis as a potential antiulcerogenic species for studies targeted towards the development of antiulcerogenic agents. © 2010 Informa Healthcare USA, Inc.